Meningkatkan Hasil Belajar Siswa Dalam Pembelajaran Seni Tari Melalui Metode Pembelajaran Cooperatif Learning Tipe Jigsaw Di SMP Negeri 3 Kota Solok - Elsa Yolanda; Fuji Astuti; Zora Iriani (FBS Universitas Negeri Padang, 2019)
This article aims to improve the learning outcomes of dance through the Jigsaw learning method for the students of SMP 3 Solok. The type of research used is classroom action research. The instrument in this study was post test and the form of assessment consisted of two forms, they were knowledge (cognitive) and skill (psychomotor) tests. The types of data in this study were primary and secondary data. The technique of collecting data was done by doing the observation, test and documentation. The data were analyzed using qualitative and quantitative analysis. To see an increase in student learning outcomes was done by comparing the percentage of students' mastery in learning before and after receiving the action. The results of the study shows that the use of the Jigsaw method in learning dance can improve students learning activities and outcomes. The percentage of completeness of students learning outcomes in the cognitive increased in cycle 2, it is 97%. Whereas, the percentage of completeness of student learning outcomes only reached 70% in cycle 1. The results of learning (psychomotor) skills of students are also very good, seen from the percentage of completeness of students learning outcomes are increase from 56.6% in cycle 2 to 90%. Then, it can be concluded that the implementation of learning with the application of Jigsaw cooperative learning can improve outcomes and students learning activities.